ANALISA KEBUTUHAN AIR BERSIH (STUDI KASUS DESA SIMPANG GAUNG KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR) - wiro saputra (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
Abstract Water is a basic need for human survival, clean water needs continue to increase while the supply of raw water infrastructure is still limited, there is often a lack of fulfillment of needs during the dry season, clean water crisis is one of the problems in Indragiri Hilir District especially in Simpang Gaung Village. Planning for a clean water distribution system really needs to be taken into account in order to guarantee the fulfillment of the level of service, in planning the clean water pipeline is determined by the water requirements and the required flow pressure. The amount or discharge of water provided depends on the population and industry served. The purpose of this study is to obtain clean water needs and a piping network system 15 based on the needs of the population in the next 15 years. The population of Simpang Gaung Village in 2018 is 4,100 people, with the semi average soul method of population growth up to 2033 is 4,283 people. The total water demand with a population of 4334 million in 2033 is 2.9420 liters / second. The source of water used is the river. Abstrak Air merupakan kebutuhan yang mendasar bagi kelangsungan hidup manusia, kebutuhan air bersih terus meningkat sementara penyediaan prasarana air baku masih terbatas, sering terjadi kekurangan pemenuhan kebutuhan saat musim kemarau, krisis air bersih merupakan salah satu masalah di Kabupaten Indragiri Hilir khusunya di Desa Simpang Gaung. Perencanaan sistem distribusi air bersih sangat perlu diperhitungkan agar dapat menjamin terpenuhinya tingkat pelayanan, pada perencanaan jaringan pipa air bersih ditentukan oleh kebutuhan air dan tekanan aliran yang diperlukan. Jumlah atau debit air yang disediakan tergantung pada jumlah penduduk dan industri yang dilayani. Tujuan dari studi ini adalah untuk mendapatkan kebutuhan air bersih dan sistim jaringan perpipaan 15 berdasarkan kebutuhan penduduk 15 tahun kedepannya. Jumlah penduduk Desa Simpang Gaung tahun 2018 berjumlah 4.100 jiwa, dengan metode semi average jiwa pertumbuhan penduduk sampai dengan tahun 2033 adalah 4.283 jiwa. Total kebutuhan air dengan jumlah penduduk 4334 juta jiwa pada tahun 2033 adalah 2,9420 liter/detik. Sumber air yang digunakan adalah sungai.